From Bits to Bodies: Perfect Humans, Bioinformatic Visualizations, and Critical Relationality - Hamilton, Jennifer A (Imaginations)

(untitled) (York University, 2019)
In December 2014, computational biologist Lior Pachter posted the results of his “tongue in cheek” in silico genome experiment on his personal blog, where he declared his discovery that “the perfect human is Puerto Rican.” In this article, I analyze the “perfect human” experiment. I argue that despite the use of 21st-century, cutting-edge technology in computing and genomics, Pachter’s experiment and his use of visualization can be usefully juxtaposed with earlier modes of visualizing heredity, namely the development of composite portraiture in the late-19th century and late-20th century technologies of “morphing.” I temper the celebration of Pachter’s creation of a “mixed race” perfect human in silico with a challenge to its ostensibly progressive stance. I instead suggest that it must be understood in the broader context of eugenic hauntings and contemporary tensions around questions of sex, sexuality, race, nation, and indigeneity. I argue that the scientific, specifically genomic, stories that we tell, can be productively read in light of critiques of biogenetic kinship and the naturalization of heterosexual love. I conclude by arguing that the perfect human experiment makes a particular kind of argument about what it means to be human and perfect and what constitutes legitimate and cognizable modes of relationality.